Efektifitas Aplikasi Alpukat Dalam Meningkatkan Pelayanan Publik Selama Pandemi Covid 19 Pada Kantor Kelurahan Jatipulo Tahun 2022 - Lina Herlina; Tulus Santoso (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to determine the effectiveness of the Alpukat Betawi application in improving public services, especially in Kelurahan Jatipulo area during the Covid-19 pandemic. This study used a descriptive qualitative method. The results showed that the application of Alpukat Betawi was good enough in serving the community in Kelurahan Jatipulo during Covid-19 pandemic, although it could not be categorized as effective because there were several Standard Operating Procedures (SOPs) that some people did not understand. The public can download the Alpukat Betawi application on their cellphones or through the website avocado- dukcapil.jakarta.go.id, and log in by entering their NIK (ID number) and password. For those who do not have an account, they can register by filling in their personal data and an active email. The user will get a verification code to input on the registration page. Only then can they enjoy the service. The problem with using the Alpukat Betawi application is that the steps still seem difficult to understand, so many people are hesitant to do the process online. Therefore, the DKI Jakarta City Government must develop the application to be more structured and make it easier for the public to use online services related to population document application.